Edexcel AS and A level Mathematics Pure Mathematics Year 1/AS Textbook. (2017) - Attwood, Greg; Barraclough, Jack; Bettison, Ian; Macpherson, Alistair; Moran, Bronwen; Nicholson, Su; Pledger, Keith; Smith, Harry; Staley, Geoff; Ward-Penny, Robert; Wilkins, Dave; Oliver, Diane; et al.
No abstract available